Speedmailing : Turn your work enemy into your best work tool - Wolfe, Richard (Pearson, 2016)
DREAMING OF AN EMPTY INBOX, BUT DON'T KNOW HOW TO MAKE IT HAPPEN? We're bombarded with messages every day, but no one tells you how to improve these vital email skills. Discover how to regain control of your email - and get back to your job - in five simple steps. Email doesn't have to be overwhelming. With Speedmailing's five-step process you can manage emails quickly and efficiently. The benefits of Speedmailing: Empties your inbox every day Increases your productivity and peace of mind Keeps your to-do list in one place Maintains a system of reminders Makes sure no.